2005
DOI: 10.1097/01.sap.0000178809.01289.10
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Human Bone Marrow Stromal Cells to Accelerate Wound Healing in Vitro

Abstract: The purpose of this pilot study was to compare proliferation, collagen synthesis, and growth factor production, which are important contributing factors for wound healing, of the bone marrow stromal cells (BSCs) with those of dermal fibroblasts in vitro. Cultured human BSCs and dermal fibroblasts from the same patients were seeded in 96-well culture plates. At 1, 3, and 5 days postincubating, cell proliferation, collagen synthesis, and secretion of basic fibroblast growth factor (bFGF), vascular endothelial gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 36 publications
4
53
1
Order By: Relevance
“…In addition to the acceleration of wound closure, the MSCs treatment strongly enhances the scar quality, which was associated to a greater quantity of collagen within the healed tissue increasing the tensile strength [13]. These cells' synthesis of larger amounts of collagen and growth factors, than native dermal fibroblasts, proves their therapeutic efficiency in cutaneous repair [14]. Together, MSC differentiation helps to regenerate damaged tissue, while their paracrine signaling accelerates reepithelialization and fibroproliferation during wound repair [15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the acceleration of wound closure, the MSCs treatment strongly enhances the scar quality, which was associated to a greater quantity of collagen within the healed tissue increasing the tensile strength [13]. These cells' synthesis of larger amounts of collagen and growth factors, than native dermal fibroblasts, proves their therapeutic efficiency in cutaneous repair [14]. Together, MSC differentiation helps to regenerate damaged tissue, while their paracrine signaling accelerates reepithelialization and fibroproliferation during wound repair [15].…”
Section: Introductionmentioning
confidence: 99%
“…In in vitro studies, MSCs have demonstrated a number of properties, which can facilitate tissue regeneration and even accelerate this process, including synthesis of some growth factors, cytokines, collagen and matrix metalloproteinases, angiogenic factors [26,28,29]. Besides, they are capable of providing migration of other skin cells such as keratinocytes [30].…”
Section: A Cellular Componentmentioning
confidence: 99%
“…Recently bone marrow, peripheral blood and umbilical cord blood have all been used as topical therapies to modulate the healing response in dermal wounds and change the nature of chronic wounds to acute wounds [29][30][31]. It is possible that fibrocytes and KLC, which are stem cells derivatives, are involved.…”
Section: Application In Plastic Surgerymentioning
confidence: 99%